KLF1 E325K-associated Congenital Dyserythropoietic Anemia Type IV: Insights Into the Variable Clinical Severity. Issue 6 (August 2018) - Ravindranath, Yaddanapudi; Johnson, Robert M.; Goyette, Gerard; Buck, Steven; Gadgeel, Manisha; Gallagher, Patrick G.
Abstract : We identified a child with KLF1 -E325K congenital dyserythropoietic anemia type IV who experienced a severe clinical course, fetal anemia, hydrops fetalis, and postnatal transfusion dependence only partially responsive to splenectomy. The child also had complete sex reversal, the cause which remains undetermined. To gain insights into our patient's severe hematologic phenotype, detailed analyses were performed. Erythrocytes from the patient and parents demonstrated functional abnormalities of the erythrocyte membrane, attributed to variants in the α-spectrin gene. Hypomorphic alleles in SEC23B and YARS2 were also identified. We hypothesize that coinheritance of variants in relevant erythrocyte genes contribute to the clinical course in our patient and other E325K-linked congenital dyserythropoietic anemia IV patients with severe clinical phenotypes. Abstract : Supplemental Digital Content is available in the text.